Las redes sociales y su relación en el rendimiento académico de los estudiantes del Primer y Segundo Año de Bachillerato de la Unidad Educativa Gonzanamá periodo marzo-octubre 2015 - Cueva Luzón, Patricio David (2015)
Social networks are social structures composed by groups of people, which are connected by one or more types of relationships; now a days young people consider social networks on Internet as essential to their daily lives, even they think social networks have little influence in areas such as family relationships, friendships or academic performance. In the present research work was intended primarily to understand the relationship of networks social and academic performance of the student in first and second of baccalaureate from the high school “Unidad Educativa Gonzanamá”; for which we look to determine the use and frequency of social networks, levels of academic performance, check whether there is a relationship between these variables and finally develop a plan of psychoeducation. An investigation of quanti type of cross-section was performed with the use of scientific methods, analytic, synthetic, descriptive, inductive deductive, supported with the use of techniques such as structured survey and questionnaire Addiction to Social Networks, through which it was possible determining that most students make use of social networks, with a frequency of once or twice a day and connecting through the cell; talking about academic performance most of students obtained scores between 7 to 8.99 points corresponding to attain the required learning, moreover, that according to student´s appreciation if there is a relationship between the use of social networks and academic performance, stating obsession with social networks. Finally is recommended the application of the proposed plan psychoeducational, to achieve guide students in the correct use of social networks Keywords: Use of social networks, academic performance, psychoeducation, interpersonal relationships, addiction,